The Intersection of Religion and Technology: Ethical Implications in the Age of AI - Phrakhrupariyatticanpandit (Journal of Exploration in Interdisciplinary Methodologies (JEIM), 2025)
This paper examines the ethical implications of AI in religious contexts, highlighting its impact on theology, spirituality, and moral governance. As AI influences religious practices and ethical decision-making, concerns regarding human dignity, algorithmic bias, and cybersecurity emerge. Using Bernard Lonergan’s critical realism and cybertheology, this study evaluates AI’s role in shaping modern religious experiences and ethical frameworks, emphasizing the need for interdisciplinary collaboration to ensure technological advancements align with spiritual and moral values. The research investigates AI’s role in shaping religious practices, from automated clergy and digital sermons to ethical decision-making frameworks informed by religious teachings. Additionally, the paper discusses the broader societal implications of AI, such as algorithmic bias, cybersecurity concerns, and the ethical dilemmas posed by Artificial Superintelligence (ASI). By analyzing contemporary theological perspectives and ethical principles, this study seeks to establish a balanced approach to integrating AI into religious life, ensuring that technological advancements align with spiritual and moral values. The findings emphasize the need for interdisciplinary dialogue among theologians, technologists, and ethicists to develop ethical AI frameworks that respect religious traditions while fostering inclusive and equitable technological progress.